FTIR-PCA analysis as an initial analysis to distinguish the origin of skin and leather - Ragil Yuliatmo; R. Lukas Martindro Satrio Ari Wibowo; Wisnu Pambudi; Sofwan Siddiq Abdullah; Thoyib Rohman Hakim; Yuny Erwanto (Majalah Kulit, Karet, dan Plastik, 2021)
Leather products are parts of daily fashion in Indonesia, such as bags, shoes, jackets, and gloves. Adulteration of raw materials for leather products can occur if there are no labels on these products. Various methods such as PCR, GC-MS, HPLC, and FTIR have been carried out to distinguish the origin of leather products. The FTIR method is known as an easy and inexpensive method to use. The objective of this study was to evaluate the capability of FTIR spectroscopy and Principle Component Analysis (PCA) for lipid identifcation and initial analysis to distinguish the original materials on leather products. Lipid extracts obtained from the various skin were scanned using an FTIR spectrophotometer at 4000–450 cm-1. It resulted in spectral diﬀerences in several wavenumbers (3000-2800 cm-1 and 1200-1000 cm-1). The same result is also found in lipid spectra from leather product extraction. The FTIR spectroscopy and PCA can diﬀerentiate pigskin and goatskin through specifc peaks in infrared spectra. This can be used as an initial analysis on determining the existence of skin adulteration in leather products. This study is prospective to be continued by chemometrics as quantitative analysis.